1993
DOI: 10.1128/aac.37.3.464
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-dose pharmacokinetics of amikacin and ceftazidime in critically ill patients with septic multiple-organ failure during intermittent hemofiltration

Abstract: The pharmacokinetic parameters of amikacin and ceftazidime were assessed in four patients undergoing hemofiltration for septic shock. The parameters were assessed during hemofiltration and in the interim period. The concentration-time profiles of these two drugs in plasma, urine, and ultrafiltrate were investigated after intravenous perfusion (30 min). In all cases a 1-g dose of ceftazidime was administered; for amikacin, the dosage regimen was adjusted according to the patient's amikacin levels (250 to 750 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In previous studies with intensive care unit (ICU) patients undergoing CRRT, amikacin clearance varied from 0.53 to 5.34 liters/h, accounting for 40 to 89% of the total body clearance (10)(11)(12)(13)(14)(15). These studies also reported conflicting results on the correlation between drug clearance and CRRT settings (11,14).…”
mentioning
confidence: 60%
“…In previous studies with intensive care unit (ICU) patients undergoing CRRT, amikacin clearance varied from 0.53 to 5.34 liters/h, accounting for 40 to 89% of the total body clearance (10)(11)(12)(13)(14)(15). These studies also reported conflicting results on the correlation between drug clearance and CRRT settings (11,14).…”
mentioning
confidence: 60%
“…Previous studies of ceftazidime pharmacokinetics in severely ill patients show a wide variation in estimated clearance and volume of distribution [31–33] although in every study, including the present one, renal function remains the major determinant of ceftazidime clearance. The pharmacokinetic properties of ceftazidime in Thai patients with septicaemic melioidosis were similar to those reported previously in patients with other causes of shock and renal failure.…”
Section: Discussionmentioning
confidence: 87%
“…D’Arcy et al [27] concluded that the use of extra renal clearance procedures could lead to an increase in the gentamicin clearance of between 10 and 40 mL/min in addition to the corresponding clearance for the same patients without renal replacement therapy. On the other hand, it has been established that the plasma half-life of the drug in patients with haemodiafiltration is much lower in patients with renal failure who are not submitted to these procedures [28]. However, the information available on the effect of the flow of the CVVHDF technique on concentrations reached by amikacin is still limited.…”
Section: Discussionmentioning
confidence: 99%